2011
DOI: 10.1002/tea.20434
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model of conceptual change in physics

Abstract: A model of conceptual change in physics was tested on introductory‐level, college physics students. Structural equation modeling was used to test hypothesized relationships among variables linked to conceptual change in physics including an approach goal orientation, need for cognition, motivation, and course grade. Conceptual change in physics was determined using gains from pre‐ to post‐administration of the Force Concept Inventory (FCI). Results indicated that need for cognition and approach goals had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 71 publications
(97 reference statements)
1
34
0
Order By: Relevance
“…intrinsic goal orientation) of SRL are essential to lead the students to use learning strategies effectively (Koksal, 2011). Intrinsically goal-oriented students, for example, are more highly motivated to learn and use deeper cognition strategies (Taasoobshirazi & Sinatra, 2011). Gürçay and Balta (2013) reported a significant (p < .05) relationship between intrinsic goal orientation and metacognitive self-regulation that explained 28 % of the variance in self-regulation in physics.…”
Section: Self-regulated Learning and Achievementmentioning
confidence: 97%
See 3 more Smart Citations
“…intrinsic goal orientation) of SRL are essential to lead the students to use learning strategies effectively (Koksal, 2011). Intrinsically goal-oriented students, for example, are more highly motivated to learn and use deeper cognition strategies (Taasoobshirazi & Sinatra, 2011). Gürçay and Balta (2013) reported a significant (p < .05) relationship between intrinsic goal orientation and metacognitive self-regulation that explained 28 % of the variance in self-regulation in physics.…”
Section: Self-regulated Learning and Achievementmentioning
confidence: 97%
“…Some researchers have suggested that personal epistemology directly and indirectly predicts students' achievement in science (Koksal, 2011;Taasoobshirazi & Sinatra, 2011). Stathopoulou and Vosniadou (2007) studied the influence of personal epistemology on achievement in classical dynamics and found that grade 10 students in Greece with low-and high-epistemological sophistication had significant (p < .001) differences in physics achievement; the sophisticated group achieved higher scores than the low (naïve) group.…”
Section: Personal Epistemology and Achievementmentioning
confidence: 97%
See 2 more Smart Citations
“…Albeit the design of the current study is driven by diSessa's knowledge in pieces approach (implying a more cognitively driven reasoning), it is of importance to consider motivational aspects as well as they are inherently interwoven (cf. Taasoobshirazi and Sinatra 2011;Zembylas 2005). When educators or test designers select contexts for learning environments, they should consider the effect that some groups of students might be advantaged or disadvantaged by certain types of contexts, be it in situations of learning or assessment.…”
Section: Synthesismentioning
confidence: 99%